“Stuff That Happened to Me”: Visual Memory in Jonathan Safran Foer’s Extremely Loud & Incredibly Close (2005) - Siegel, Elisabeth (Current Objectives of Postgraduate American Studies, 2012)
The article examines the use of graphic images for mnemonic purposes in Jonathan Safran Foer’s Extremely Loud & Incredibly Close“ (2005). It argues that through the combination of photographs with magical realist and fantastic passages, the novel provides a commentary on the role of visual representations in the construction of a collective memory of 9/11.